PERSEPSI KEUNTUNGAN DAN TINGKAT KEPERCAYAAN DALAM MEDIA SOSIAL SEBAGAI DETERMINAN INTENSI UMKM DENGAN KENYAMANAN SEBAGAI VARIABEL INTERVENING - Ikhsan Habib Fabillah; Erni Febriani; Ayu Aulia; Silvia Prisca Gani (Universitas La Tansa Mashiro, 2026)
This study aims to explore the impact of perceived benefits and perceived trust on MSMEs' intention to transact on social media platforms, with perceived convenience as a mediating variable. The methodology used is a quantitative approach by conducting a survey of 292 MSMEs in Lampung Province who actively use social media for transactions. The data obtained were analyzed through Structural Equation Modeling with the Partial Least Squares (PLS-SEM) approach. The findings of this study indicate that both perceived benefits and perceived trust have a positive and significant influence on perceived convenience. In addition, perceived benefits, perceived trust, and perceived convenience also have a positive and significant influence on MSMEs' intention to transact through social media. The results indicate that perceived convenience functions as a partial mediator for the influence of perceived benefits and perceived trust on MSMEs' intention.